Tourism stakeholders perception on tourists’ expenditure in entertainment sector in Melaka UNESCO World Heritage area - Ab Rahman, Syakir Amir; Mohamed Osman, Mariana; Bachok, Syahriah; Ibrahim, Mansor; Mohamed, Mohd Zin (2016)
This study examined the perception of government officers and tourism players on tourists’ expenditure pattern in entertainment activities in Melaka UNESCO World Heritage area. A total of 28 interviewees were interviewed using judgemental sampling technique. Content analysis was used to identify and evaluate the perceptions. Results revealed that 22 interviewees responded positive results on the finding of tourists spent less in entertainment (RM22.50 and below) while six interviewees responded negative response. These findings suggested several courses of action to enhance the cultural and recreational entertainment in the study area to increase the tourists’ expenditure.